Performance Analysis of a Rod Breakdown System - Z Taj, S; M Rizwan, S; M Alkali, B; K Harrison, D; Taneja, G (International Journal of Engineering and Technology, 2018)
The paper presents performance analysis of a rod breakdown system consisting of two machines operating in parallel. Ten years maintenance data of the system depicts three maintenance practices: repair, major preventive maintenance and minor preventive maintenance. Machines are repaired on normal failures, whereas major/minor preventive maintenance is carried out at scheduled basis. The machines are queued for major preventive maintenance. An operative machine requires a cooling period of half hour before undergoing major preventive maintenance. Repair is prioritized over major preventive maintenance. The system is analysed using semi-Markov processes and regenerative point techniques. Performance indices namely mean time to system failure, system availability, no. of system repairs and busy period of the repairman are obtained. Simulated results are presented to demonstrate the effect of varying failure/repair rates on the system performance. Â Â